Interactive Multimedia Multimedia Production and Digital Storytelling - Cvetković, Dragan (IntechOpen, 2019)
Multimedia is the common name for media that combine more than one type of individual medium to create a single unit. Interactive media are the means of communication in which the outputs depend on the inputs made by the user. This book contains 11 chapters that are divided into two sections: Interactive Multimedia and Education and Interactive Multimedia and Medicine. The authors of the chapters deal with different topics within these disciplines, such as the importance of cloud storage, development of play tools for children, use of gaming on multimedia devices designed for the elderly, development of a reading, writing, and spelling program based on Luria's theories, as well as development of mobile applications called BloodHero dedicated to the increase in blood donors, etc.